A speed-of-play limit reduces gambling expenditure in an online roulette game: Results of an online experiment. (April 2022) - Newall, Philip W.S.; Weiss-Cohen, Leonardo; Singmann, Henrik; Paul Boyce, W.; Walasek, Lukasz; Rockloff, Matthew J.
Highlights: Direct test of policy proposal to slow the speed of online gambling games to their land-based casino equivalent speed. Commercial online roulette game used and edited to create realistic stimuli. Participants bet with incentivized funds on randomized and fair outcomes. Abstract: UK online casino games are presently not subject to any limitations on speed-of-play or stakes. One recent policy proposal is to ensure that no online casino game can be played faster than its in-person equivalent. Another policy proposal is to limit the maximum stakes on online casino games to £2, to match the current stake limit on electronic gambling machines. This research experimentally investigated the speed-of-play proposal subject to a £2 stake limit, in an online experiment using incentivized payouts based on £4 endowments and a commercial online roulette game, which was slowed-down in one condition to enforce a speed-of-play limit of one spin every 60 seconds. UK residents, aged 18 years and over and with experience in playing online roulette (N = 1, 002), were recruited from an online crowdsourcing panel. In the slowed-down condition there was a credible reduction in the amount gambled. This effect occurred via a credible reduction in the mean number of spins which outweighed any potential increases in bet sizes. Speed-of-play limits may be effective in reducing gambling expenditure for online roulette.